Neuroprotective potential of Spirulina platensis on lesioned spinal cord corticospinal tract under experimental conditions in rat models - Abdullahi, Dauda; Annuar, Azlina Ahmad; Sanusi, Junedah (Taylor & Francis, 2019)
Spinal cord injury (SCI) results from penetrating or compressive traumatic injury to the spine in humans or by the surgical compression of the spinal cord in experimental animals. In this study, the neuroprotective potential of Spirulina platensis was investigated on ultrastructural and functional recovery of the spinal cord following surgical-induced injury. Twenty-four Sprague-Dawley rats were divided into three groups; sham group, control (trauma) group, and experimental (S. platensis) group (180 mg/kg) of eight rats each. For each group, the rats were then subdivided into two groups to allow measurement at two different timepoints (day 14 and 28) for the microscopic analysis. Rats in the control and experimental S. platensis groups were subjected to partial crush injury at the level of T12 with Inox number 2 modified forceps by compressing on the spinal cord for 30 s. Pairwise comparisons of ultrastructural grading mean scores difference between the control and experimental S. platensis groups reveals that there were significant differences on the axonal ultrastructure, myelin sheath and BBB Score on Day 28; these correlate with the functional locomotor recovery at this timepoint. The results suggest that supplementation with S. platensis induces functional recovery and effective preservation of the spinal cord ultrastructure after SCI. These findings will open new potential avenue for further research into the mechanism of S. platensis-mediated spinal cord repair. © 2019, © 2019 Taylor & Francis Group, LLC.